Immune correlates of protection for dengue: State of the art and research agenda. Issue 36 (24th August 2017) - ,; Baric, Ralph; Coller, Beth-Ann; Coloma, Josefina; Crowe, James E.; Cummings, Derek A.T.; Dean, Hansi; de Silva, Aravinda; Diamond, Michael S.; Durbin, Anna; Ferguson, Neil; Gilbert, Peter B.; et al.
Abstract: Dengue viruses (DENV1-4) are mosquito-borne flaviviruses estimated to cause up to ∼400 million infections and ∼100 million dengue cases each year. Factors that contribute to protection from and risk of dengue and severe dengue disease have been studied extensively but are still not fully understood. Results from Phase 3 vaccine efficacy trials have recently become available for one vaccine candidate, now licensed for use in several countries, and more Phase 2 and 3 studies of additional vaccine candidates are ongoing, making these issues all the more urgent and timely. At the " Summit on Dengue Immune Correlates of Protection ", held in Annecy, France, on March 8–9, 2016, dengue experts from diverse fields came together to discuss the current understanding of the immune response to and protection from DENV infection and disease, identify key unanswered questions, discuss data on immune correlates and plans for comparison of results across assays/consortia, and propose a research agenda for investigation of dengue immune correlates, all in the context of both natural infection studies and vaccine trials.